Bevacizumab in Combination with folfiri Chemotherapy in Patients with Metastatic Colorectal Cancer: An Assessment of Safety and Efficacy in the Province of Newfoundland and Labrador - G. Dranitsaris; S. Edwards; J. Edwards; M. Leblanc; R. Abbott (Current Oncology, 2010)
Background: In 2005, bevacizumab was approved by Health Canada for patients with metastatic colorectal cancer (mcrc). Newfoundland and Labrador was one of the first Canadian provinces to fund this agent in combination with FOLFIRI (irinotecan, 5-fluorouracil, leucovorin) chemotherapy. In this analysis, the entire provincial bevacizumab sample for the first 2 years was assessed for overall safety and efficacy. Methods: The medical records of 43 patients with mcrc who had received FOLFIRI with bevacizumab were identified and reviewed. The longitudinal data collection format that was adopted assessed occurrences of adverse events after each cycle of treatment. Toxicity outcomes such as gastrointestinal (GI) perforations, bleeding, diarrhea, myelosuppression, proteinuria, and venous thromboembolic events (VTES) were collected and graded using the U.S. National Cancer Institute’s Common Terminology Criteria for Adverse Events, version 3.0. Time to treatment failure (TTF) and overall survival (os) were determined using the Kaplan–Meier method. Results: Overall, the 43 study patients received 398 cycles of anticancer therapy (median: 6 cycles; range: 1–24 cycles). No GI perforations were identified. However, 4 bleeding events occurred (9.3%), 3 requiring permanent discontinuation of bevacizumab. Also, 6 grade 3 or 4 VTES occurred (14.0%), 3 of which required a hospital admission. In addition, grades 3 and 4 diarrhea, febrile neutropenia, and proteinuria showed cumulative incidences of 11.6%, 2.3%, and 2.3% respectively. Median TTF was 6.3 months; median os was 24.4 months. Conclusions: Bevacizumab in combination with FOLFIRI appears to be well tolerated, and efficacy is consistent with trial reports. However, patients should be closely monitored to avoid potentially serious events such as bleeding and VTES.